V dialogu s jinou-než-lidskou přírodou. Přínos a meze Abramovy posthumanistické ekofenomenologie - Prášek, Petr (Filosoﬁcký časopis)
The paradox of the Anthropocene is that humankind has become the planetary superpower, and yet faces an unprecedented ecological crisis as well as other forces that it is not capable of controlling. The solution is not to be found in putting faith in technological innovations that do not yet exist, but in a completely new attitude of humanity towards itself and all non-human beings and entities: posthumanism. Nature in fact speaks with more voices than only human ones, and humans have always and are still able to listen to these other voices. However, according to ecophenomenologist David Abram, this listening is becoming increasingly difficult, for these voices are being drowned out by the purely human logic of abstract thought and scientific-technical society. The article focuses on the meaning of Abram’s ideas from the point of view of posthumanism and ecophenomenology as such. By means of this, it tries to demonstrate in what lies the import of phenomenology when it is applied to one of the greatest challenges of our time and why it should go still further in this regard than did Abram.